68Ga-FAPI-PET/CT improves diagnostic staging and radiotherapy planning of adenoid cystic carcinomas – Imaging analysis and histological validation. (July 2021) - Röhrich, Manuel; Syed, Mustafa; Liew, Dawn P.; Giesel, Frederik L.; Liermann, Jakob; Choyke, Peter L.; Wefers, Annika K.; Ritz, Thomas; Szymbara, Marina; Schillings, Lisa; Heger, Ulrike; Rathke, Hendrik; et al.
Graphical abstract: Highlights: FAPI-PET/CT shows high and specific uptake in primary and metastatic ACCs. FAPI-PET/CT led to upstaging and altered target volume delineation (compared to CT/MRI). FAPI-PET/CT may have marked impact on staging and radiotherapy planning of ACCs. Abstract: Background: Adenoid cystic carcinomas (ACCs) are rare epithelial tumors mostly situated in the head and neck region and characterized by infiltrative growth. The tumor stroma of ACCs includes cancer-associated fibroblasts (CAFs) expressing Fibroblast Activation Protein (FAP), a new target for positron emission tomography (PET) imaging. Here we describe the value of PET/ computed tomography (PET/CT) imaging using 68 Ga-labelled FAP-Inhibitors ( 68 Ga-FAPI-PET/CT) and their clinical potential for staging and radiotherapy planning in 12 ACC patients (7 primary, 5 recurrent). Patients and methods: Patients underwent contrast enhanced staging CT (ceCT) and magnetic resonance imaging (ceMRI) before 68 Ga-FAPI - PET/CT. PET-scans were acquired 10, 60 and 180 minutes after administration of 150–250 MBq of 68 Ga-labelled FAPI tracers. SUVmax and SUVmean values of ACCs and healthy organs were obtained using a 60% of maximum iso-contour. FAP and alpha smooth muscle actin (α-SMA) immunohistochemistry was performed in 13 cases (3 with and 10 without 68 Ga FAPI-PET/CT). Staging and radiotherapy planning based on 68 Ga-FAPI-PET/CT versus ceCT/MRI alone were compared. Results: We observed elevated tracer uptake in all ACCs. Immunohistochemistry showed FAP-expressing CAFs in the tumor. Compared to conventional staging, 68 Ga-FAPI-PET/CT led to upstaging in 2/12 patients and to detection of additional metastases in 3 patients, thus in total 42% of patients had their staging altered. Moreover, 68 Ga-FAPI PET improved the accuracy of target volume delineation for radiotherapy, as compared to CT and MRI. Conclusion: 68 Ga-FAPI-PET/CT is a promising imaging modality for ACC, increasing the accuracy of staging exams and radiotherapy planning volumes, as compared conventional to CT and MRI.